2023
DOI: 10.1590/1809-4392202201212
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic occurrence in fish species from the Iquitos region in Peru, western Amazonia

Abstract: The contamination of aquatic environments by microplastic has become a major threat to biodiversity. The presence of microplastic is documented in the aquatic fauna of the oceans, but, in the Amazon basin, reports on microplastic occurrence are few. The present study surveyed microplastic occurrence in fishes in an area of the Peruvian Amazon. We sampled 61 specimens of 15 commercial species from local markets in the city of Iquitos, Loreto Department. We detected a total of 2337 microplastic particles, 1096 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Fibers predominated in both cases, comprising more than 80% of the MPs. However, only Chota-Macuyama and Mendoza [ 55 ] determined the polymeric composition of the particles, by digestion (NaOH 10 mol.L −1 for 120 h), which may account for the difference of one order of magnitude from the results of Rojas et al [ 54 ]. Additionally, Iquitos is a large urban center (146,853 inhabitants, 24.76 inhabitants.km −2 ) that continually suffers a process of unregulated urbanization, resulting in the rapid proliferation of periurban settlements exposed to poor sanitation conditions along the margins of the rivers that surround the city [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Fibers predominated in both cases, comprising more than 80% of the MPs. However, only Chota-Macuyama and Mendoza [ 55 ] determined the polymeric composition of the particles, by digestion (NaOH 10 mol.L −1 for 120 h), which may account for the difference of one order of magnitude from the results of Rojas et al [ 54 ]. Additionally, Iquitos is a large urban center (146,853 inhabitants, 24.76 inhabitants.km −2 ) that continually suffers a process of unregulated urbanization, resulting in the rapid proliferation of periurban settlements exposed to poor sanitation conditions along the margins of the rivers that surround the city [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 61%
“… Purchased from local market Necropsy, digestion (10 Mol. L−1 NaOH, 120 h), sieving (0.075 μm mesh) Microscopy Cleaning of worksurfaces, blank control 38.3 MPs.individual −1 [ 54 ] S. aequifasciatus Experiment Lyophilization, digestion (HNO 3 , 70 °C, 2 h) Fluorescence spectroscopy [ 11 ] S. aequifasciatus Experiment [ 45 ] Sediment River sediment Van Veen grab Sieving (63 μm mesh), digestion (H 2 O 2 , room temperature, 24 h), flotation (1.70 kg.L −1 ZnCl 2 ), filtration (18 μm mesh) Microscopy Use of non-plastic instruments 417–8178 MP kg −1 [ 19 ] Beach sediment Hand trowel Sieving (2000 and 500 μm meshes) Microscopy Not described 987–761 MP kg −1 [ 44 ] Beach sediment Excavation of quadrants Sieving (250, 500 and 5000 μm meshes), flotation (1.15 kg.L −1 NaCl), filtration Microscopy Plastic cover on microscope, petri dishes to airborne contamination 492.5 MP m −3 [ 18 ] Beach sediment Excavation of quadrants Sieving (300 μm mesh),...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, pollution from microplastics is another serious issue that has been escalating in recent years (Rojas et al, 2023). Studies have shown that the presence of microplastics in the stomachs of fish has significantly increased from the mid-century to the present, correlating with the rise in plastic concentration in the environment (Hou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%